Effects of Seasonal Changes and Ground Ice on Electromagnetic Surveys of Permafrost - Arcone ,Steven A; Delaney ,Allan J; Sellmann,Paul V (1979)
The performance of surface impedance and magnetic induction electromagnetic subsurface exploration techniques was studied seasonally at various sites in Alaska where permafrost and massive ground ice occurred. The surface impedance method, which uses radiowaves in the LF and VLF bands, and the magnetic induction method, which uses low-frequency magnetic induction fields, distinguish subsurface materials by the electrical resistivity of the materials. The methods used have greatest sensitivity within about 20 m of the surface and are, therefore, most applicable for shallow subsurface investigations. The selection of study sites was based on anticipated contrasts in electrical resistivity between ground ice and adjacent earth materials. A magnetic induction instrument, using a separation of 3.66-m between the transmitter and receiver antennas, in general was able to detect near-surface zones of massive ice and to provide data regarding permafrost distribution in both the Fairbanks and Prudhoe Bay areas. At this antenna separation, the depth of magnetic field penetration was sufficient to include mainly the zone containing maximum contrasts in resistivity between ground ice and other earth materials. In the Fairbanks area, contrasts, in this zone were greatest in late winter when the seasonally thawed surface layer was completely frozen. When thawed, this layer usually becomes more conductive and often masks the deeper resistivity contrasts. In the Prudhoe Bay area, maximum ground resistivity contrasts were detected in late summer when shallow subsurface temperatures had risen sufficiently to permit resistivity contrasts between the massive ice and the ice-rich ground to appear.